The impact of BREXIT vote on the Risk Governance of UK Financial Institutions - Petrou, Georgios (2019)
Inevitably, the catastrophic consequences, of the recent financial crisis, have led to radical changes in all aspects, with some of them taking place within, a recently developed section of Corporate Governance known as, Risk Governance. The aim of this dissertation is to subject this information to examination and analysis in an attempt to arrive at reasonable conclusions on the impact of the BREXIT vote on the use by Listed UK Financial Institutions of Chief Risk Officers (CROs) and Risk Committees in their Risk Governance. The Descriptive Analysis of the data shows the changes in the CRO and Risk Committee ratios throughout the sample period. Both ratios have increased since 2012, with Risk Committee capturing higher ratios during the entire 2012-2018 period, but with CRO experiencing the largest percentage change. The change in the ratios cannot be considered as significant and attributable to the BREXIT Referendum, since both ratios follow a more or less an anticipated path. However, dividing the data by sectors, can provide a more clear image of how the trends of each ratio changes throughout the timeline provided, showing that Banks and Insurance related Institutions have experienced the most significant changes in both ratios. The overall analysis for CRO indicates that Risk Committee Meetings and Board Diversity are the most important Independent variables since they are the only two being significant in all models. During the second period Board and Risk Committee Sizes were added in the significant variables with all four variables having a positive association with the CRO ratio. This outcome is interpreted as, the larger the values of such attributes the more likely an organisation is to appoint a CRO. Furthermore, the Risk Committee analysis revealed Board Size and Board Meetings as strongly significant during both sample periods and Board Independence only for the second period.